2017
DOI: 10.1111/plb.12527
|View full text |Cite
|
Sign up to set email alerts
|

Karyotype diversity and genome size variation in Neotropical Maxillariinae orchids

Abstract: Orchidaceae is a widely distributed plant family with very diverse vegetative and floral morphology, and such variability is also reflected in their karyotypes. However, since only a low proportion of Orchidaceae has been analysed for chromosome data, greater diversity may await to be unveiled. Here we analyse both genome size (GS) and karyotype in two subtribes recently included in the broadened Maxillariinea to detect how much chromosome and GS variation there is in these groups and to evaluate which genome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 66 publications
2
5
0
Order By: Relevance
“…Our information on the nuclear DNA contents of B. striata showed that the 2C values in populations with dysploidy (2n = 2x = 34; 2n = 2x = 36) were not significantly different from those in other B. striata populations with 2n = 2x = 32 (Table 1). Indeed, dysploidy events are considered the most important chromosome evolutionary mechanism in Orchidaceae (Grabiele et al, 2013;Moraes et al, 2017), and the increase from 2n = 32 to 2n = 36 in B. striata was consistent with this hypothesis. Therefore, to fully support polyploidy and dysploidy as important evolutionary mechanisms in the genus Bletilla, chromosome banding techniques and/or in situ hybridization need to be used, which will enable particular chromosome rearrangements to be tracked.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Our information on the nuclear DNA contents of B. striata showed that the 2C values in populations with dysploidy (2n = 2x = 34; 2n = 2x = 36) were not significantly different from those in other B. striata populations with 2n = 2x = 32 (Table 1). Indeed, dysploidy events are considered the most important chromosome evolutionary mechanism in Orchidaceae (Grabiele et al, 2013;Moraes et al, 2017), and the increase from 2n = 32 to 2n = 36 in B. striata was consistent with this hypothesis. Therefore, to fully support polyploidy and dysploidy as important evolutionary mechanisms in the genus Bletilla, chromosome banding techniques and/or in situ hybridization need to be used, which will enable particular chromosome rearrangements to be tracked.…”
Section: Resultssupporting
confidence: 73%
“…The variations in chromosome numbers also reflected frequent dysploidy events detected in Orchidaceae (Felix and Guerra, 2010;Mandakova and Lysak, 2018;Moraes et al, 2017). Dysploids with 2n = 2x = 36 and 2n = 2x = 34 in B. striata were found in this study.…”
Section: Resultssupporting
confidence: 68%
“…These factors may be responsible for chromosome variability, which appears to occur freely in buthids, as well as the expansion of gene families and neofunctionalization, as described by Cao et al [ 70 ] and Sharma et al [ 73 ]. Alternatively, as proposed for angiosperms [ 74 76 ], polyploidy/paleopolyploidy followed by repeated disploidy events also lead to the high variability of diploid numbers during meiosis I. In scorpions, however, the whole-genome duplication has been debated (for reviews, see [ 70 , 77 ]).…”
Section: Discussionmentioning
confidence: 99%
“…The main factors that influence plant chromosome evolution are chromosome rearrangement and polyploidy [ 19 , 20 , 21 , 22 ]. The breakage and subsequent ligation of chromosomal segments can lead to rearrangements of the chromosome structure, such as inversions, translocations, centric split and fusion, duplications, and deletions.…”
Section: Chromosome Evolution In Plantsmentioning
confidence: 99%